Kamus Lima Bahasa dengan Metode Binary Search dan Levenshtein Distance Berbasis Android - Ibrahim, Muhammad Yusuf; , Nurgiyatna, ST., MSc., PhD (2016)
Dictionary is a reference used to find the meaning or translation of a word. Dictionary comes in many different forms but nowadays dictionary application in smartphone is widely used for its flexibility. So the aim of this research was to make five language dictionary android based application. This application can be used to translate words from Indonesian, English, Germany, Spanish, France and vice versa. This application was developed using ECLIPSE. This application used levenshtein distance algorithm and binary search methods. These methods simplified searching and translating of a word using this application. This application showed translation from one language to four other languages at once. The result of external survey from 30 respondents using questionnaire showed that 86% respondents satisfied with the interface and feature of this application